Benefits of physical exercise on Parkinson's disease disorders induced in animal models - Luciana Renata da Conceição; Leandro Pereira de Moura; José Rodrigo Pauli (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: The preventive and therapeutic role of physical exercise in Parkinson's disease (PD) has been the target of study of many scientific groups, and the research often is done in experimental models, especially rodents. Thus, the aim of this review was to analyze a database, elucidating the main benefits that the systematized practice of physical activity/ exercises can contribute to PD in animal models. Method: Based on this question, a search on PubMed and Medline database containing the terms: "Parkinson's disease" AND "animal model" AND "physical exercise" was performed. The most pertinent studies were selected by the criteria year of publication (2009- 2018) and the original article. It was used papers involving animal models and physical exercises, as well as other studies, which allowed an introductory explanation in PD, covering its pathophysiology, and the neurochemical responses of physical exercise in rodents. Results: The results showed that there was a decrease in the levels of nigrostriatal neurodegeneration and an increase in the neuroprotective effect related to the training program. Conclusion: It was concluded that physical exercise has been pointed as an important neuroprotective strategy in animal models of Parkinson's disease, especially those applied at moderate intensities, which were effective in reducing the inflammatory profile, elevating the expression of genes and proteins related to neuronal restoration, mitochondrial biogenesis, repair of the dopaminergic system, besides other events also capable of reflecting improvements in motor and cognitive behavior of animals.